Estetika Mendhalungan Pertunjukan Wayang Kulit Banyumasan Lakon Srikandhi Mustikaningrat Sajian Bagas Kriswanto - Willy Setia Budi; Wicaksono, Andi (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2024)
This study aims to reveal the aesthetics mendhalungan on the Banyumasan style puppet show Srikandhi Mustikaningrat presented by Bagas Kriswanto. This research is expected to enrich the elements of performance aesthetics, and can be used as reference material for similar studies. The characteristic of Banyumasan style lies in the elements of pakeliran work, namely catur, sabet and pakeliran music. In this regard, the play Srikandhi Mustikaningrat in Banyumasan style presented by Bagas Kriswanto is explored using the theory of performance aesthetics which aims to describe the performance aesthetics with the concept of mendhalungan. This research uses the qualitative method by Moleong, which uses literature review, observation, interviews, transcription, and data analysis. To analyze the aesthetics of this performance using the concept of mendhalungan proposed by Bagong Pujiono. This research shows that the achievements of the mendhalungan concept were successfully presented by Bagas Kriswanto. This is proven by achieving harmony between the five elements in one performance.